2012
DOI: 10.1111/all.12054
|View full text |Cite
|
Sign up to set email alerts
|

Local receptor revision and class switching to IgE in chronic rhinosinusitis with nasal polyps

Abstract: Our results provide the first evidence of local receptor revision and class switching to IgE, and B-cell differentiation into IgE-secreting plasma cells in NP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
139
3
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 38 publications
(45 reference statements)
11
139
3
6
Order By: Relevance
“…However, IgE also can be produced from GC-independent sources, because B cell lymphoma 6-deficient or lymphotoxin-a-deficient mice produce IgE, despite having defective formation of GCs or lymph nodes, respectively (48,49). Furthermore, although local production of IgE in mucosal tissues is important in allergic disease, and some studies suggested the local formation of GC-like structures (50,51), it is not clear how GC responses are important for local IgE production (46). Our results demonstrate that MyD88 also may mediate GCindependent IgE production, if any, in lungs exposed to ragweed pollen, because IgE responses were totally abrogated in Myd88 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, IgE also can be produced from GC-independent sources, because B cell lymphoma 6-deficient or lymphotoxin-a-deficient mice produce IgE, despite having defective formation of GCs or lymph nodes, respectively (48,49). Furthermore, although local production of IgE in mucosal tissues is important in allergic disease, and some studies suggested the local formation of GC-like structures (50,51), it is not clear how GC responses are important for local IgE production (46). Our results demonstrate that MyD88 also may mediate GCindependent IgE production, if any, in lungs exposed to ragweed pollen, because IgE responses were totally abrogated in Myd88 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…913 Most importantly, IgE antibodies to enterotoxins (SE-IgE) were associated with significantly higher concentrations of IgG, specifically of the IgG4 subclass, and IgE in NPs. 914 In CRSwNP, evidence for local IgE synthesis and class switch recombination was also provided 915 ; recombination activating genes RAG1 and RAG2 mRNA concentrations were increased in polyps and correlated with the magnitude of inflammation and the presence of SE-specific IgE in the NP mucosa, pointing to a very active local Ig production in SEIgE positive polyps. The locally formed IgE is polyclonal, with IgE antibodies against several hundred or more allergens, and functional, even in the absence of systemic IgE antibodies or a positive skin-prick test.…”
Section: Viiib Crswnp: Comorbid Asthmamentioning
confidence: 99%
“…84,85 Inflammatory response amplification via bacterial super-antigens is also observed and leads to enhanced nasal IgE production. 86 In contrast, CRSsNP is characterized by a distinct inflammatory pattern, with a Th1 cell bias and excess interferon-c (IFN-c) and neutrophilic inflammation. 87 Whilst both CRS phenotypes have a high incidence of lower airway disease with asthma and bronchiectasis, the poor ability to subtype CRSsNP inflammatory profiles makes it difficult to compare remodelling changes with those occurring in the lower airway.…”
Section: Ch Ronic R Hin Osin Usitis and Sinon Asal Remodellingmentioning
confidence: 99%